Implementation of a Web-Based Goods Delivery Service System Using the Waterfall Method - Novrindah Alvi Hasanah; Luthfi Atikah (Universitas Negeri Surabaya, 2025)
The development of information technology is driving changes in people's transaction patterns, particularly in online buying and selling activities. However, not all consumer needs can be met through available e-commerce platforms, especially for certain products that are limited or not always available. Therefore, consignment services have become a popular alternative solution. This study aims to implement a web-based consignment service system that can facilitate the ordering process, product data management, and transactions between customers and service providers in a structured and efficient manner. The system development method used is the Waterfall method, which consists of the stages of needs analysis, system design, implementation, testing, and maintenance. The system built has two main types of users, namely admin and customer, with different interfaces and access rights. The implementation results show that the system is able to support the online consignment service process, from product search, ordering, transaction management, to report presentation, thereby increasing the ease, speed, and accuracy of the web-based consignment service.